Effect of Employee Performance Activities on The Mang Bagja Application on The Performance Allowances Received By Employees at The Bandung City Cipta Karya, Construction and Spatial Planning Office - Maria Oktaviani Delbi Bia Mampu; Widwi Handari Adji (International Research & Development for Human Beings (IRDH), 2025)
This research seeks to explore the impact of employee performance activities related to the Mang Bagja application on the performance allowances awarded to employees at the Bandung City Cipta Karya, Construction Development, and Spatial Planning Office. This research employs an associative quantitative methodology, utilizing a data collection technique that involves distributing questionnaires to a sample of 54 employees. The independent variable in this investigation is the employee performance activities within the Mang Bagja application, whereas the dependent variable pertains to the performance allowance awarded to employees. The findings of this analysis indicate a robust correlation between employee performance activities and the allowances received by employees, evidenced by a correlation coefficient value of 0.837. A straightforward regression analysis revealed that each enhancement in employee performance activities significantly influenced the increase in performance allowance by 0.893. The T-test score of 11.039 surpasses the t-table value of 2.006 (11.039>2.006), indicating a significant influence of employee performance activities on the Mang Bagja application regarding the allowances received by employees. The Coefficient of Determination (R²) of 0.701 shows that employee performance activities in the Mang Bagja application explain 70.1% of the differences in the allowances employees receive, with the remaining 29.9% due to other factors not looked at in this study. The findings suggest that the Mang Bagja application plays a beneficial role in evaluating and distributing performance allowances while also fostering transparency and accountability and enhancing employee motivation within the governmental context.